Phytoplankton community structure in relation to hydrographic features along a coast-to-offshore transect on the SW Atlantic Continental Shelf. (1st December 2017) - Islabão, C.A.; Mendes, C.R.B.; Detoni, A.M.S.; Odebrecht, C.
Abstract: The continental shelf in Southern Brazil is characterized by high biological productivity associated with horizontal and vertical density gradients due to the mixing of distinct water masses. Phytoplankton biomass and composition were evaluated in summer 2013 along an on-offshore transect off the mouth of the Patos Lagoon (Lat. 32°12S). Photosynthetic active radiation, temperature, salinity and fluorescence vertical profiles were carried out and Brünt-Väisäla frequency was estimated. Three water bodies were identified: the Subtropical Shelf Water along the entire transect, the Plata Plume Water on the middle shelf surface and the Tropical Water farther offshore. The water was sampled (N = 40) for the analyses of dissolved inorganic nutrients, phytoplankton cell density and composition. Phytoplankton present in the water was identified and quantified by the classical microscope sedimentation technique, complemented with CHEMTAX analysis of high-performance liquid chromatography (HPLC) pigment data. From the results obtained, chlorophyll a concentration was higher at both coastal stations (1.6–2.0 mg m −3 ) where the water column was homogeneous and diatoms dominated the stations. This group was replaced by dinoflagellates in stratified conditions on the shelf and farther offshore. Along the onshore-offshore gradient, two types of dinoflagellates were found: the peridinin-containing dinoflagellates Prorocentrum and Scrippsiella with a small contribution at the coastal stations, and the fucoxantin-containing small Gymnodiniales cells (< 15 µm) with more than 50% of the total chlorophyll a at the stations on the continental shelf, especially associated with the chlorophyll maximum at the base of the euphotic zone. The positive (negative) relationship between the biomass of dinoflagellates (diatoms) with the Brünt-Väisäla frequency, respectively, support the hypothesis that stratification is the most important environmental factor that determines the biomass of phytoplankton communities and distribution on the shelf and in coastal waters off Southern Brazil in summer. Picoplankton cells ( Prochlorococcus and Synechococcus ), recorded for the first time in the region under study, were predominant in the nutrient-poor and well-lit surface layers along the transect, indicating the importance of their low sedimentation rates (small size) and photo-adaptive strategies to survive on the upper layers of the water column. Highlights: The relationship between phytoplankton and hydrographic features was investigated. Diatoms were predominant at the mixed coastal stations. Dinoflagellates with Fucoxantin were predominant on the shelf. Picoplankton cells were more representative in surface samples with low nutrients. There was a positive relationship between dinoflagellates and the La Plata water.